How green is my politics? Cock, J and Koch, E (eds) (1991) Going green: People, politics and the environment in South Africa. Cape Town: Oxford University Press. - Baker, Carolyn (PINS-Psychology in Society, 2026)
Going Green sets itself out to inform its readers about some of the most urgent environmental issues within the political framework of South Africa, both historically and at present. The editors, Jacklyn Cock and Eddie Koch and seventeen other contributors ranging from ecologists, through journalists to trade unionists have collectively addressed ecological/environmental problems facing South Africa, and attempted to show the atrocious damage done to our environment and in particular as a result of apartheid politics. There are seventeen chapters and ten profiles on some of the more active people within South Africa’s green movement. Each page has bold type quotes extracted from the text and highlighting some of the more startling perspectives in each chapter. Profiles are brief but informative and serve to introduce readers to some of the people who have contributed to the green movement in South Africa. Selected references for each chapter follow at the end of the book.